Analysing the efficacy and tolerability of dolutegravir plus either rilpivirine or lamivudine in a multicentre cohort of virologically suppressed PLWHIV. (22nd October 2022) - Ciccullo, A; Baldin, G; Borghi, V; Cossu, M V; Giacomelli, A; Lagi, F; Farinacci, D; Iannone, V; Passerotto, R A; Capetti, A; Sterrantino, G; Mussini, C; et al.
Abstract: Objectives: We aimed to investigate and compare the efficacy and safety of two dolutegravir-based two-drug regimens: dolutegravir + lamivudine versus dolutegravir + rilpivirine. Methods: We analysed a cohort of people living with HIV (PLWHIV) switching to dolutegravir + lamivudine or dolutegravir + rilpivirine. We excluded from the analysis PLWHIV with no available pre-switch genotypic test or with a known resistance mutation to one of the study drugs. We evaluated incidence of virological failure (VF) and treatment discontinuation (TD), as well as changes in immunological and metabolic parameters. Results: We enrolled 592 PLWHIV: 306 in the lamivudine group and 286 in the rilpivirine group. We observed nine VFs in the lamivudine group [1.4 VF per 100 patient-years of follow-up (PYFU)] and four VFs in the rilpivirine group (0.6 VF per 100 PYFU). Subsequent genotypic analysis showed no acquired resistance-associated mutations in those experiencing VF. Estimated probability of maintaining virological suppression at 144 and 240 weeks were 96.6% and 92.7%, respectively, in the lamivudine group and 98.7% and 98.7%, respectively, in the rilpivirine group (log-rank P  = 0.172). The estimated probability of maintaining study regimen at Week 240 was 82.3% in the lamivudine group and 85.9% in the rilpivirine group (log-rank P  = 0.018). We observed a significant improvement in CD4+ cell count at Week 240 in the lamivudine group ( P  = 0.012); in the rilpivirine group we registered a significant increase in CD4/CD8 ratio ( P  = 0.014). Conclusions: Both analysed strategies are effective and safe as switch strategies in clinical practice, with a low incidence of VF and a favourable immunological recovery, even in the long term.